Theoretical Study of Elliptic Drum of Vertical Spindle Cotton Picker - Ravutov , Shavkat; Rakhimov, Abdumalik; Ibragimov, Gafurjan (IIUM Engineering Journal, 2025)
The article focuses on the structural optimization of the planetary mechanism of the spindle drum of a vertical-spindle cotton-picking machine in Uzbekistan and discusses the problems of synthesizing a new vertical-spindle drum that significantly enhances the efficiency of using spindles and increases the productivity of the machine. Utilizing the interaction characteristics of drum spindles with cotton plants and ensuring the effective functioning of spindle friction drives, it is theoretically justified that the trajectory of spindle relative motion has an elliptical shape. Special attention is given to the shape and dimensions of the directional path, ensuring the elliptical movement of the spindles. An analytical expression is obtained, and a convenient calculation algorithm is developed to automate the investigation of the influence of the dimensions of drum mechanism parts on the directional path shape and its dimensions. The theoretical results allow for preliminary conclusions regarding the dynamic processes occurring during drum operation and provide recommendations for selecting the directional path shape and dimensions. ABSTRAK: Artikel ini memberi tumpuan kepada pengoptimuman struktur mekanisme planet bagi dram gelendong mesin pemetik kapas gelendong-menegak di Uzbekistan, serta membincangkan permasalahan dalam mensintesis dram gelendong menegak baharu yang dapat meningkatkan kecekapan penggunaan gelendong dan produktiviti mesin secara signifikan. Dengan mengambil kira ciri interaksi antara gelendong dram dan pokok kapas serta memastikan keberkesanan operasi pemacu geseran gelendong, didapati secara teori bahawa trajektori pergerakan relatif gelendong berbentuk elips. Perhatian khusus diberikan kepada bentuk dan dimensi arah laluan yang menjamin pergerakan elips gelendong. Satu ungkapan analitik telah diperoleh dan algoritma pengiraan yang sesuai telah dibangunkan bagi tujuan automasi penyelidikan terhadap pengaruh dimensi komponen mekanisme dram terhadap bentuk dan dimensi laluan arah. Dapatan teori yang diperoleh membolehkan rumusan awal dibuat berkaitan proses dinamik yang berlaku semasa operasi dram dan seterusnya memberikan cadangan dalam pemilihan bentuk serta dimensi laluan arah.